Aerosols as a source of dissolved black carbon to the ocean - Hongyan Bao (Nature Portfolio, 2017)
The contribution of atmospheric deposition to the oceanic dissolved black carbon pool (DBC) is unclear. Here, the authors show that water-soluble black carbon is positively correlated with water-soluble organic carbon in marine aerosols, and that atmospheric deposition is a significant source of oceanic DBC.